Knowledge Accounts. Issue 3 (June 2016) - Massingham, Peter
Abstract : This paper presents a method for measuring the value of individual knowledge. There has been considerable previous research, largely driven by practitioners, who desire a rigorous method for measuring intangible assets. However, no consensus has been reached. This paper uses measurement theory and measurement purpose as criteria for evaluating our method. The method is grounded in intellectual capital theory, and also draws on psychometrics and social network analysis theory. The method was tested over three annual surveys (2009–2011) as part of a large-scale longitudinal change project. The results are explained in terms of validity and reliability testing as well as how the KA model works and how it may be used for internal management, external reporting and regulatory reporting. The findings reveal practical outcomes for managers and shareholders.